BENNABI’S THOUGHTS ON CIVILIZATION: ANALYZING FROM A PLURALISTIC PERSPECTIVE: الاسلام و الحضارة: دراسة لافكار بن نبي - Subhani, Zulqernain Haider; Md Noon, Hazizan; Ahmed, Younus (Journal of Al-Tamaddun, 2020)
Malek Bennabi was a prominent social thinker and Muslim reformer post-world war II. His thoughts on civilization and in particular, Islamic civilization stand remarkable and spectacular. Growing up in a colonial period and under the tyranny of colonizers, where not only the physical condition of his people was at stake, but also their identity and intellectual capacity were in jeopardy. He was, thus, prompted to analyze the root of the problem of colonization. After a long-deliberated analysis, he concluded that the problem of any people lies in things related to their civilization. Consequently, he extensively engaged with the discourses on civilization. He looked at civilization as an equation of three elements, which are man, soil, and time, where religious ideas, or any alternative ideology, act as a catalyst for constructing a civilization. The aim of this paper is, thus, to analyze Bennabi’s thoughts in the light of new developments in the discourse on civilization, especially in the field of historical sociology and social anthropology. To achieve this goal, his works are consulted and analyzed alongside other significant works on civilization, modernity, and religion. This conceptual paper was developed based on qualitative research. It presents the idea of multiple civilizations as opposed to the dichotomy of Islamic and Western/Christian civilizations. The analysis of Bennabi’s thought from a pluralistic perspective rejects the notion of any clash among civilizations, more specifically between modern and Islamic civilizations. It also challenges Bennabi’s view on the genealogy of modern civilization in terms of religion. Moreover, the study gives appropriate theoretical foundations to analyze Muslim world/s spanning over more than a millennium. Bennabi is not viewing the whole Muslim history and the world as a single civilization and juxtaposing it with that of West. His main contention is that all civilizations have their genesis in religion or ideology for their existence.